Determinants of customer trust in fintech as a means of payment through an approach technology acceptance model - Adele Mailangkay; Edhi Juwono (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2023)
The development of technology and information is growing rapidly along with the emergence of the digital era. This study aims to determine and analyze the determinants of customer trust in fintech as a means of payment through the technology acceptance model approach. The research method uses quantitative descriptive analysis with a sample of 150 respondents. The results showed that perceived ease of use had a positive and significant effect on perceived usefulness. The perception of ease of use and the perception of usability have a positive and significant effect on attitudes. The perception of usefulness and attitude have a positive and significant effect on the intention to use fintech. Therefore, FinTech is seen as a good opportunity by regulators as supervisors and organizers, and by the community as users of FinTech.